Digital Transformation in Villages: A Policy Implementation Approach in Kajowair Village, Nusa Tenggara Timur - Beatrix Brightany Hieng; Ni Putu Anik Prabawati (Baileo)
The digital transformation of public services in rural areas represents a pivotal effort in bridging the urban-rural divide, yet its implementation faces unique challenges at the micro level. This study examines the policy implementation of the Village Management and Service Information System (Simpeldesa) in Kajowair Village, Nusa Tenggara Timur (NTT), highlighting its distinct approaches compared to other villages. Employing a qualitative descriptive method, this research engaged 15 key participants, including village leaders, administrative officials, and community members. Data collection encompassed in-depth interviews, direct observations of Simpeldesa operations, document analysis, and literature reviews. Findings reveal that Simpeldesa implementation demonstrates a commitment to digital transformation, with strong disposition from village officials and strategic bureaucratic structures fostering effective coordination. However, challenges remain, particularly in communication and infrastructure. Limited program socialization and reliance on orbit-based internet coverage impede broader community engagement and optimal service delivery. Despite these obstacles, the allocation of substantial resources and the program’s initial success—evidenced by 50% progress in administrative data integration—underscore the potential of Simpeldesa to improve rural governance. This study contributes to the theoretical development of policy implementation by emphasizing the role of communication, resource allocation, disposition, and simplified bureaucratic structures in the success of digital transformation at the village level. Practical recommendations include enhancing community outreach and expanding infrastructure support to ensure inclusive and sustainable digitalization. The findings provide a framework for other rural areas seeking to adopt similar innovations, advancing both theoretical and practical discourse in social and human sciences.